 5.39. EQUIVALENT FILTERS AND REBASE OF FILTERS

130

Antisymmetry. Suppose

X v Y

and

Y v X

. Then

S

X v

S

Y

and

S

Y v

S

X

.

Thus

S

X

=

S

Y

and so

S

x

=

S

y

for some

x

∈ X

,

y

∈ Y

. Consequently

S

(

x

÷

B

) =

S

(

y

÷

B

) for

B

= Base(

x

)

t

Base(

y

). Thus

x

÷

B

=

y

÷

B

and so

x

y

, thus

X

=

Y

.

Theorem

722

.

[

x

]

v

[

y

]

x

v

y

for filters

x

and

y

with the same base set.

Proof.

. Obvious.

. Let Base(

x

) = Base(

y

) =

B

. Suppose [

x

]

v

[

y

]. Then there exist

x

0

x

and

y

0

y

such that

C

= Base(

x

0

) = Base(

y

0

) (for some set

C

) and

x

0

v

y

0

.

We have by the lemma

x

0

÷

(

B

t

C

)

v

y

0

÷

(

B

t

C

).

But

x

0

÷

(

B

t

C

) =

x

÷

(

B

t

C

) and

y

0

÷

(

B

t

C

) =

y

÷

(

B

t

C

). So

x

÷

(

B

t

C

)

v

y

÷

(

B

t

C

) and thus again applying the lemma

x

v

y

.

Proposition

723

.

X v Y ⇒ X ÷

C

v Y ÷

C

for every unfixed filters

X

,

Y

and set

C

.

Proof.

Let

X v Y

. Then there are

x

∈ X

,

y

∈ Y

such that Base(

x

) = Base(

y

)

and

x

v

y

. Then by proved above

x

÷

C

v

y

÷

C

what is equivalent to

X ÷

C

v

Y ÷

C

.

Proposition

724

.

If

C

S

X

and

C

S

Y

for unfixed filters

X

and

Y

then

X ÷

C

v Y ÷

C

⇔ X v Y

.

Proof.

. Previous proposition.

. Let

X ÷

C

v Y ÷

C

. We have some

x

∈ X

,

y

∈ Y

, such that Base(

x

) = Base(

y

)

and

x

÷

C

v

y

÷

C

. So

S

(

x

÷

C

)

v

S

(

y

÷

C

). But

S

(

x

÷

C

)

x

and

S

(

y

÷

C

)

y

. Thus

S

x

v

S

y

that is

x

v

y

and so

X v Y

.

5.39.4. Rebase of unfixed filters.

Proposition

716

allows to define:

Definition

725

.

A ÷

B

=

a

÷

B

for an unfixed filter

A

and arbitrary

a

∈ A

.

Obvious

726

.

(

X ÷

A

)

÷

B

=

X ÷

B

if

B

v

A

for every unfixed filter

X

and

sets

A

,

B

.

Proposition

715

allows to define:

Definition

727

.

S

A

=

S

a

for every

a

∈ A

for every unfixed filter

A

.

Theorem

728

.

S

is an order-isomorphism from the poset of unfixed filters to

the poset of filters on

Z

.

Proof.

We already know that

S

is an order embedding. It remains to prove

that it is a surjection.

Let

Y

be a filter on

Z

. Take

Z

3

X

∈ Y

. Then

h

X

ui

Y

is a filter on

X

and

S

[

h

X

ui

Y

] =

S

h

X

ui

Y

=

Y

. We have proved that it is a surjection.

Obvious

729

.

A ÷

B

=

h

B

ui

S

A

for every unfixed filter

A

.

Obvious

730

.

If

A

S

A

then

A ÷

A

∈ A

for every unfixed filter

A

.

Proposition

731

.

If

C

S

X

and

C

S

Y

for unfixed filters

X

and

Y

then

X ÷

C

=

Y ÷

C

⇔ X

=

Y

.